Synthesis and characterization of [4‐(CH2O)2CHC6H4]2Hg, [4‐(O=CH)C6H4]2Hg and [(E)‐4‐(RN=CH)C6H4]2Hg (R = 2′‐py, 4′‐py, 2′‐pyCH2, 4′‐pyCH2). (25th June 2021) - Kiss, Levente; Pop, Alexandra; Shova, Sergiu; Raț, Ciprian I.; Silvestru, Cristian
Abstract: The reaction of 4‐[(CH2 O)2 CH]C6 H4 Br (1 ) with n ‐BuLi, followed by addition of HgCl2 to the in situ formed organolithium derivative, affords [4‐(CH2 O)2 CHC6 H4 ]2 Hg (2 ). Deprotection of the formyl groups of 2 in presence of p ‐TsOH ( p ‐Ts = 4‐MeC6 H4 SO3 ) leads to [4‐(O=CH)C6 H4 ]2 Hg (3 ). Condensation reactions of 3 with 2‐aminopyridine (2‐pyNH2 ), 4‐aminopyridine (4‐pyNH2 ), 2‐aminomethylpyridine (2‐pyCH2 NH2 ), and 4‐aminomethylpyridine (4‐pyCH2 NH2 ), in CH2 Cl2, affords the novel diorganomercury(II) compounds of type [( E )‐4‐(RN=C)C6 H4 ]2 Hg [R = 2′‐py (4 ), 4′‐py (5 ), 2'‐pyCH2‐ (6 ), 4′‐pyCH2 (7 )]. Compounds 2 and 3 were useful precursors for the preparation of the corresponding homocoupling products [4‐(CH2 O)2 CHC6 H4 ]2 (8 ) and [4‐(O=CH)C6 H4 ]2 (9 ) in presence of catalytic amounts of palladium(II) acetate. Compounds 2 –9 were characterized by multinuclear magnetic resonance (NMR) ( 1 H, 13 C 1 H, and 199 Hg 1 H, when appropriate) and infrared (IR) spectroscopy and by mass spectrometry. The molecular structures of 3, 5, 6, 8, and 9 were determined by single‐crystal X‐ray diffraction. Abstract : Highlights: A quick, easy, and economic synthesis was optimized for bis(4‐formylphenyl)mercury(II). Syntheses of novel homoleptic diorganomercury(II) compounds with imine functional groups were optimized to give good to excellent yields in mild conditions with easy workup. All diorganomercury(II) compounds were characterized by multinuclear ( 1 H, 13 C 1 H, and 199 Hg 1 H NMR) and IR spectroscopy as well as mass spectrometry and, for three compounds with imine functional groups, the molecular structure was determined by single‐crystal X‐ray diffraction. The use of diorganomercury(II) compounds as starting materials for homocoupling reactions, in presence of catalytic amounts of palladium(II) acetate, was investigated.